2017
DOI: 10.1101/167577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association analyses identify 44 risk variants and refine the genetic architecture of major depressive disorder

Abstract: Major depressive disorder (MDD) is a notably complex illness with a lifetime prevalence of 14%.1 It is often chronic or recurrent and is thus accompanied by considerable morbidity, excess mortality, substantial costs, and heightened risk of suicide.2-7 MDD is a major cause of disability worldwide. 8 We conducted a genome-wide association (GWA) meta-analysis in 130,664 MDD cases and 330,470 controls, and identified 44 independent loci that met criteria for statistical significance. We present extensive analyses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 127 publications
(155 reference statements)
1
48
0
1
Order By: Relevance
“…At the Bonferroni-corrected p-value threshold of .0006 (i.e., .05/80 tests), the GRS constructed from SNPs with p-values < 0.001 in the combined PGC MDD2 and 23andme cohorts (Wray et al, 2017) were significantly associated with all four depression phenotypes (Supplemental Table 17) - original depressive symptom score : β = 0.012, 95% CI=(0.006,0.017), p = .00004; adjusting for medication use : β = 0.013, 95% CI=(0.007,0.019), p = .00004; excluding medication users : β = 0.011, 95% CI=(0.005,0.017), p = .0001; binary depression: OR = 1.001, 95% CI=(1.000, 1.001), p = .0004. The p < 10 −4 GRS was also significantly associated with depression in the analysis excluding medication users ( p = .0004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the Bonferroni-corrected p-value threshold of .0006 (i.e., .05/80 tests), the GRS constructed from SNPs with p-values < 0.001 in the combined PGC MDD2 and 23andme cohorts (Wray et al, 2017) were significantly associated with all four depression phenotypes (Supplemental Table 17) - original depressive symptom score : β = 0.012, 95% CI=(0.006,0.017), p = .00004; adjusting for medication use : β = 0.013, 95% CI=(0.007,0.019), p = .00004; excluding medication users : β = 0.011, 95% CI=(0.005,0.017), p = .0001; binary depression: OR = 1.001, 95% CI=(1.000, 1.001), p = .0004. The p < 10 −4 GRS was also significantly associated with depression in the analysis excluding medication users ( p = .0004).…”
Section: Resultsmentioning
confidence: 99%
“…An r-value < .05 indicates that the SNP is associated in the same direction in both the discovery GWAS and HCHS/SOL GWAS. We studied the generalization of genetic associations from European ancestry populations to Hispanics/Latinos, using the three largest GWAS of depression to date (Direk et al, 2016; Okbay et al, 2016; Wray et al, 2017) as the discovery datasets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could have led to the different sets of cases having different genetic architectures. However, the experience of the PGC (and other groups) provides strong evidence that, if this is true, the adverse impact is small relative to the large benefits of an increased sample (7, 32). Finally, the SE and DK collections enable linkage with other national registers that can provide a comprehensive characterization of psychiatric and somatic comorbidity, whereas these auxiliary data are not available in the US and ANZ.…”
Section: Discussionmentioning
confidence: 99%
“…Twin and family studies robustly demonstrate that genetic factors play a role in risk for MD, with heritability estimates of roughly 35% for MD and 45% for early-onset MD 9 . The largest meta-analysis of molecular genetic studies of MD recently identified 44 independent loci, underscoring the centrality of genetic factors in the etiology of MD 10 . Twin study variance component analyses also indicate a considerable contribution of unique environmental risk factors to MD 11 .…”
Section: Introductionmentioning
confidence: 99%